2023
DOI: 10.1186/s12933-023-01897-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of sodium-glucose co-transporter-2 inhibitors or glucagon-like peptide-1 receptor agonists versus sulfonylureas and the risk of lower limb amputations: a nation-wide cohort study

Abstract: Background Numerous studies have investigated the potential association of sodium-glucose co-transporter-2 inhibitors (SGLT2-Is) with an increased risk of lower limb amputations (LLAs), but have produced conflicting results. Particularly studies comparing SGLT2-Is to glucagon-like peptide-1 receptor agonists (GLP1-RAs) seem to find a higher LLA risk with SGLT2-I use. This raises the question whether the results are driven by a protective GLP1-RA-effect rather than a harmful SGLT2-I-effect. GLP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This could assist clinicians decide not just to initiate anti-hyperglycemia therapy, but also a complete strategy that could postpone the progression of diabetic foot ulcer. [29][30][31][32] Firstly, after adjusting for the duration of diabetes, blood glucose, and HbA1c, we found an aging tendency of DFU in both genders' distributions, suggesting that aging is an independent risk factor in the DFU group; we also revealed that sdLDL, a component of LDL and atherogenic particle, was significantly decreased in patients with DFU, but not TC, TG, HDL, or LDL levels. Furthermore, as a major independent risk factor for cardiovascular disorders, LP(a) was shown to be higher in the DFU group, suggesting that LP(a) may be a metabolic risk for cardiovascular disease in DFU patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This could assist clinicians decide not just to initiate anti-hyperglycemia therapy, but also a complete strategy that could postpone the progression of diabetic foot ulcer. [29][30][31][32] Firstly, after adjusting for the duration of diabetes, blood glucose, and HbA1c, we found an aging tendency of DFU in both genders' distributions, suggesting that aging is an independent risk factor in the DFU group; we also revealed that sdLDL, a component of LDL and atherogenic particle, was significantly decreased in patients with DFU, but not TC, TG, HDL, or LDL levels. Furthermore, as a major independent risk factor for cardiovascular disorders, LP(a) was shown to be higher in the DFU group, suggesting that LP(a) may be a metabolic risk for cardiovascular disease in DFU patients.…”
Section: Discussionmentioning
confidence: 63%
“…This could assist clinicians decide not just to initiate anti-hyperglycemia therapy, but also a complete strategy that could postpone the progression of diabetic foot ulcer. 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular outcomes were also improved in patients with DM type 2 receiving GLP-1 receptor agonist treatment in some, but not all, clinical trials [ 325 ]. In a retrospective cohort study of patients with PAD and DM under either SGLT-2 inhibitors, GLP-1 receptor agonists or sulfonylureas, GLP-1 receptor agonist prescription was associated with a significantly lower rate of lower limb amputation [ 326 ]. Metformin used to be considered the established first-line therapy for patients with DM type 2 for decades [ 327 ].…”
Section: Current and Novel Therapeutic Targets And Strategiesmentioning
confidence: 99%